Age-Dependent Disparities in the Prevalence of Single and Clustering Cardiovascular Risk Factors: A Cross-Sectional Cohort Study in Middle-Aged and Older Adults - Macek P (Dove Medical Press, 2020)
Pawel Macek,1,2 Marek Zak,2 Malgorzata Terek-Derszniak,3 Malgorzata Biskup,2,3 Przemyslaw Ciepiela,4 Halina Krol,2,5 Jolanta Smok-Kalwat,6 Stanislaw Gozdz2,6 1Department of Epidemiology and Cancer Control, Holycross Cancer Centre, Kielce, Poland; 2Faculty of Medicine and Health Sciences, The Jan Kochanowski University, Kielce, Poland; 3Department of Rehabilitation, Holycross Cancer Centre, Kielce, Poland; 4Clinic of Oncological Surgery, Holycross Cancer Centre, Kielce, Poland; 5Research and Education Department, Holycross Cancer Centre, Kielce, Poland; 6Clinic of Clinical Oncology, Holycross Cancer Centre, Kielce, PolandCorrespondence: Marek ZakFaculty of Medicine and Health Sciences, The Jan Kochanowski University, Al. IX Wiekow Kielc 19, Kielce 25-317, PolandTel +48 41 349 6909Fax +48 41 349 6916Email mkzak@ujk.edu.plBackground: Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide; with age acknowledged as an independent cardiovascular risk factor (CRF) in adults. Appreciating the association between age and classic CRFs is believed to boost all potential benefits of prevention.Purpose: Assessment of the prevalence of single and clustered CRFs and their association with age.Patients and Methods: The survey involved 4735 people (33.6% men) who were PONS project attendees aged 45– 64. The study protocol comprised the Health Status Questionnaire, general medical examination, anthropometric measurements, and blood and urine sampling. The prevalence of single and clustered CRFs (hypertension, dyslipidemia, diabetes mellitus, and obesity) in the incrementally split age groups was calculated. The incidence rate of CRFs, against their absence, was determined by Poisson regression models with robust standard errors.Results: The prevalence of CRFs was established in 90% of the respondents. Except dyslipidemia and ≥ 1 CRFs, prevalence of risk factors increased with age, although this trend was the weakest in men. In the total group, and in women, prevalence of dyslipidemia and ≥ 1 CRFs was unrelated to age, whereas in men, it was on the rise in the younger age groups. The incidence rate of CRFs was strongly related to age, and, with the exception of dyslipidemia, was higher in the older age groups.Conclusion: Cardiovascular risk factors are common in the adult population, while their prevalence and clustering are more prevalent in seniors. Apart from dyslipidemia, the risk of CRFs is appreciably age-related, and higher in seniors.Keywords: age, cardiovascular disease, risk factors, prevalence, public health